Three-dimensional woodpile photonic crystals for visible light applications. (21st August 2017) - Dhuey, Scott; Testini, Angelica; Koshelev, Alexander; Borys, Nicholas; Piper, Jessica R; Melli, Mauro; Schuck, P James; Peroz, Christophe; Cabrini, Stefano
Abstract: Three-dimensional woodpile photonic crystals for the visible light regime were fabricated using a layer-by-layer electron beam lithography process. The materials consisted of silicon nitride for the high index material and the planarization was accomplished using a spin-coated nano-porous silica material which was left in place as the interstitial material. This fabrication procedure presents a simplified route for constructing multilayer structures where planarization is necessary, including three-dimensional photonic crystals (3DPCs) or three-dimensional metamaterials. To demonstrate the robustness of the approach, multiple 3DPCs were fabricated and optically characterized. Multiplane waveguide defects were inserted in the crystals and characterized. The vertical waveguides demonstrate enhanced transmission of light, and work continues to realize waveguiding through the full three-dimensional network of waveguides.